Physical education lessons in waldorf pedagogy: a case study (Research, Society and Development, 2019)
This article aims to describe and understand the Waldorf pedagogy teaching system (PW) in physical education classes. The case study uses participant observation and interview in data collection. The subject is a teacher at a private school in Cuiabá Mato-Grosso, with children from 6 to 14 years old and bibliographic review. The research school has as a methodology focused on development through play, learning by playing, this pedagogy was founded by Rudolf Steiner, having in its methodology an individualized look in search of human formation. It will be investigated how this teaching pedagogy applies in Physical Education classes, as well as knowing the educational objectives to be achieved by students who appreciate this teaching proposal in German. Therefore, it is important that learning is enjoyable in a humane way without the need for mechanical teaching. Components were presented about the playfulness in PP, applied in Physical Education classes, as behaviors and attitudes in different situations. Live with others, feelings, expressions and others. It then appears that PW uses Ludicity at EDF to train intellectually and spiritually developed, capable and free people ready for life.